2014
DOI: 10.5152/tjar.2014.67044
|View full text |Cite
|
Sign up to set email alerts
|

The Decrease of the Duration of Stay in the ICU with Rib Fixation in a Case of Multiple Rib Fracture

Abstract: Severe breathing problems arise in multiple rib fractures. As a result, many advantages of the surgical stabilization of the chest wall have been reported. Especially, shortening mechanical ventilation, along with a decrease in the duration of intensive care unit stay, is important for the prevention of possible infection complications. In this study, the dramatic improvement of the breathing pattern, as well as the reduction in ventilator duration after rib fixation time, of a 36-year-old patient with severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The number of claws ranges from 8 to 18. 21,22 We found that a higher number of claws is associated with a greater titanium plate length, resulting in increased dissociation of the muscles around the fractured ribs. The four-claw titanium plate was invented in 2012 by a doctor in our department.…”
Section: Discussionmentioning
confidence: 84%
“…The number of claws ranges from 8 to 18. 21,22 We found that a higher number of claws is associated with a greater titanium plate length, resulting in increased dissociation of the muscles around the fractured ribs. The four-claw titanium plate was invented in 2012 by a doctor in our department.…”
Section: Discussionmentioning
confidence: 84%